FALSAFAH KAMASE-MASE SUKU KAJANG DALAM PENERAPAN TATA KELOLA KEBIJAKAN PENGENDALIAN PEMANFAATAN RUANG - Sitti Rabiatul Wahdaniyah Herman; Supriadi Takwim (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
The Kamase-mase philosophy is the local wisdom of the Kajang Tribe which shows a form of morality in regulating the joints of their lives, including policy governance in controlling space utilization. The Kajang people are taught to live simply and preserve the natural surroundings by being honest, curbing lust, not harming others, and not being materialistic. Local wisdom as part of the practical rationale in spatial planning policies that complement scientific knowledge should be considered as a local potential that can be collaborated and communicated. The context of spatial planning policy is not only physical, but also regulates human behavior as the main factor that has an influence on space. Spatial planning policies regulate the form of social structures and interactions between community groups, referred to as governance which includes the authority of customary leaders, rules, sanctions, and social fines to form a value system that regulates the ethics of evaluating good and bad and the right and wrong of a thought and action. The Kamase-mase philosophy becomes an ideology in living life and affects the treatment of space, where space is used according to needs, so that all aspects of life such as food, clothing, gardens, rice fields, and houses are simple or not excessive, including the use of forest resources.